Peran Adrenoseptor B-Prasinaptik dalam Patofisiologi Hipertensi - Ngatijan Ngatijan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
The pathophysiological concept of hypertension is still in debate since many factors are involved in the development of the disease. Stress plays a role in the pathophysiology of hypertension through its effect on adrenaline secretion and sympathetic tone.In the development of adrenoceptor concept some studies showed that presynaptic P.adrenoceptors are of (32 subtype. Since the evidence for noradrenaline activating presynaptic 13-adrenoceptors is mostly negative, the question arises whether presynaptic 13-adrenoceptors have a physiological activator. Many studies showed that adrenaline is suggested to be the putative activator through its role as cotransmitter.Since there was correlation between stress; and the increase in the concentration of plasma adrenaline and blood pressure, it is suggested that presynaptic fl-adrenoceptor has an important role in the development of hypertension.Key Words: adrenaline — cotransrnitter — hypertension — presynaptic B— adrenoceptors — sympathetic transmission